Climate services in practice: An outcome evaluation of Vietnam's agro-climatic bulletin approach - Nguyen, Van; Blundo Canto, Genowefa (2025)
This study evaluates Vietnam’s Agro-Climatic Bulletin (ACB) approach—an innovative, government-led climate service designed to support climate-resilient agricultural planning across the Mekong River Delta. Developed under the DeRISK SE Asia project, ACBs are co-produced by Technical Working Groups integrating weather forecasts, agricultural data, and adaptive recommendations for farmers, and are disseminated via digital, audio, and print formats. Using outcome harvesting, innovation history, and semi-structured interviews with 33 stakeholders across eight provinces, the evaluation identified 123 reported outcomes across areas such as farmer practices, institutional communication, capacity building, and scaling. Results show improved inter-agency coordination, enhanced technical capacity, more responsive agro-advisories, and increased local adaptation and ownership of the ACB model. However, challenges such as lack of formal institutionalization, funding uncertainty, and limited farmer-level impact evidence persist. The study recommends formalizing ACBs within government policy frameworks, investing in automation and farmer-level research, supporting communication innovations, and strengthening multi-level coordination to scale and sustain the approach.